PERLAKUAN AKUNTANSI AKTIVA TETAP BERWUJUD DAN PENYAJIANNYA DALAM LAPORAN KEUANGAN PADA CV. BAHANA KARYA GRESIK - CATUR AGUS ISMAWATI (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Accounting is one of the means to manage the tangible fixed assets to suit the needs of the company. Accounting has the basics of accounting process begins when the tangible fixed assets acquired tangible fixed assets to tangible fixed assets are released or waived. Issues to be discussed further in this study is